2018
DOI: 10.1016/j.bbrc.2018.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EMT mediated tyrosine kinase inhibitor resistance in NSCLC

Abstract: In the United States, lung cancer is the second most common cancer in men and women. In 2017, 222,500 new cases and 155,870 deaths from lung cancer are estimated to have occurred. A tyrosine kinase receptor, epidermal growth factor receptor (EGFR), is over expressed or mutated in non-small cell lung cancer (NSCLC) resulting in increased cell proliferation and survival. Tyrosine kinase inhibitors (TKIs) are currently being used as therapy for NSCLC patients, however, they have limited efficacy in NSCLC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…Interestingly, TKI-resistant NSCLC cells also exhibited low levels of E-cadherin expression and high expression of EMT markers such as Twist, Slug and Snail. This is in contrast to TKI-sensitive NSCLC cells, where E-cadherin was expressed and low levels of the aforementioned EMT markers were observed [69]. Given the dependence of the Kaiso-p120 ctn interaction on the status of p120 ctn phosphorylation [68], it is possible that p120 ctn is hyper-phosphorylated in TKI-resistant NSCLC cells, resulting in its sequestration by Kaiso and consequently, a reduction in E-cadherin protein stability concomitant with increased cell motility or metastasis.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Inmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, TKI-resistant NSCLC cells also exhibited low levels of E-cadherin expression and high expression of EMT markers such as Twist, Slug and Snail. This is in contrast to TKI-sensitive NSCLC cells, where E-cadherin was expressed and low levels of the aforementioned EMT markers were observed [69]. Given the dependence of the Kaiso-p120 ctn interaction on the status of p120 ctn phosphorylation [68], it is possible that p120 ctn is hyper-phosphorylated in TKI-resistant NSCLC cells, resulting in its sequestration by Kaiso and consequently, a reduction in E-cadherin protein stability concomitant with increased cell motility or metastasis.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Inmentioning
confidence: 98%
“…They further showed that higher levels of Kaiso co-precipitated with phosphorylated p120 ctn compared to unphosphorylated p120 ctn , suggesting that serine-288 phosphorylation may act as the molecular switch that mediates p120 ctn -Kaiso binding in lung cancer cells [68]. Most recently, Iderzorig et al [69] found that p120 ctn co-localizes with Kaiso in the nucleus in tyrosine kinase inhibitor (TKI)-resistant NSCLC cells, while in TKI-sensitive NSCLC cells reduced co-localization was observed. Interestingly, TKI-resistant NSCLC cells also exhibited low levels of E-cadherin expression and high expression of EMT markers such as Twist, Slug and Snail.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Inmentioning
confidence: 99%
“…The gatekeeper mutants of EGFR, PDGFR, c-ABL, and Src were shown to have activated kinase activity and an increased rate of cellular transformation (16). In addition, the EGFR T790M gatekeeper mutation has been shown to promote EMT (28)(29)(30). Previous studies in our lab have kinetically characterized V561M FGFR1 and demonstrated an increase in the k cat of V561M FGFR1 relative to wild type (WT).…”
Section: Introductionmentioning
confidence: 94%
“…For instance, silencing PRMT1 decreased a mitogenic factor called Neuromedin B receptor while increased epithelial markers cytokeratins 7 and 8, which consequently resulted in reduced cell proliferation and enhanced tumor differentiation [ 134 ]. Additionally, up-regulated PRMT1 repressed E-cadherin activity and promoted EMT in erlotinib-resistant NSCLC cells (erlotinib is a tyrosine kinase inhibitor against NSCLC) [ 135 ].…”
Section: Histone Arginine Methylation/demethylation In Lung Cancermentioning
confidence: 99%